2014
DOI: 10.1159/000358843
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis Care and Dialysis Outcomes in Hemodialysis Patients with a Functioning Fistula

Abstract: Background/Aims: Predialysis care has been associated with improved first-year outcomes. We investigated types of predialysis care associated with improved patient outcomes in patients initiating dialysis with a fistula and at least 2 years of predialysis care. Methods: In this retrospective cohort of incident hemodialysis patients with ≥2 years of Medicare coverage before dialysis initiation, care patterns and patients were determined using Medicare claims. Fistula use at initiation was ascertained from the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
2
10
0
3
Order By: Relevance
“…Because AVF require several weeks to mature and approximately 40% of created AVF never mature [4] , AVF creation is reliant on predialysis care, especially predialysis nephrology referral [5][6][7] . While studies of the development and maturation of AVF have focused on clinical factors [8][9][10][11] , the role of socioeconomic factors, particularly individual-level poverty, has not been reported in a recent national cohort of dialysis patients, although a previous study reported that county-level poverty was inversely associated with incident AVF use, but not with subsequent improvement in AVF use in prevalent patients [12] .…”
Section: Impact Of Poverty and Healthmentioning
confidence: 99%
“…Because AVF require several weeks to mature and approximately 40% of created AVF never mature [4] , AVF creation is reliant on predialysis care, especially predialysis nephrology referral [5][6][7] . While studies of the development and maturation of AVF have focused on clinical factors [8][9][10][11] , the role of socioeconomic factors, particularly individual-level poverty, has not been reported in a recent national cohort of dialysis patients, although a previous study reported that county-level poverty was inversely associated with incident AVF use, but not with subsequent improvement in AVF use in prevalent patients [12] .…”
Section: Impact Of Poverty and Healthmentioning
confidence: 99%
“…Gillespie et al [16] found that pre-ESRD nephrology care for >12 months was significantly associated with initial AVF or graft use vs. catheter (aOR 11.3). Further, Chan et al [3] observed a 61% reduction in early death risk in those patients who initiated dialysis with an AVF, consistent with many studies demonstrating lower morbidity and mortality associated with AVF vs. catheter use [18,19,20,21,22,23,24,25,38,39]. In our study, the likelihood of catheter use at dialysis initiation was reduced by 67% among MHS vs. non-MHS patients, which could partly explain the improved survival in the MHS cohort, given the attenuation of its survival advantage after adjusting for vascular access types in the regression model.…”
Section: Discussionmentioning
confidence: 55%
“…One of the primary focuses of pre-ESRD care is the creation of an arteriovenous fistula (AVF), as recommended by the Kidney Disease Improving Global Outcomes to be the vascular access of choice for patients needing maintenance HD [17] due to its longevity and lower rates of infection and intervention. Many studies demonstrate that HD using an AVF is associated with improved survival and fewer hospitalizations compared with the complication-prone dialysis catheters [18,19,20,21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Yapılan birçok çalışmada, rutin HD'e giren hastaların prediyaliz döneminde düzenli nefrolog takibine gelmesi ve AVF kullanımının özendirilmesi, gerekli eğitim verilmesi hastaların mortalite ve morbiditesine anlamlı katkı sağlar (8,(23)(24)(25). Çalışmamızda AV fistül kullanımı beklenen ve hedeflenen oranların altında bulunmuştur.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…Öncesinde herhangi bir eğitim ve hazırlık yapılmaksızın programsız olarak acil HD'e alınan hastalarda ilk HD sıklıkla kateter yolu ile yapılmaktadır (25,27,28).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified